Histidine‐rich glycoprotein promotes macrophage activation and inflammation in chronic liver disease. Issue 4 (19th February 2016) - Bartneck, Matthias; Fech, Viktor; Ehling, Josef; Govaere, Olivier; Warzecha, Klaudia Theresa; Hittatiya, Kanishka; Vucur, Mihael; Gautheron, Jérémie; Luedde, Tom; Trautwein, Christian; Lammers, Twan; Roskams, Tania; et al.
Abstract : Pathogen‐ and injury‐related danger signals as well as cytokines released by immune cells influence the functional differentiation of macrophages in chronic inflammation. Recently, the liver‐derived plasma protein, histidine‐rich glycoprotein (HRG), was demonstrated, in mouse tumor models, to mediate the transition of alternatively activated (M2) to proinflammatory (M1) macrophages, which limit tumor growth and metastasis. We hypothesized that liver‐derived HRG is a critical endogenous modulator of hepatic macrophage functionality and investigated its implications for liver inflammation and fibrosis by comparing C57BL/6N wild‐type (WT) and Hrg −/− mice. In homeostatic conditions, hepatic macrophages were overall reduced and preferentially polarized toward the anti‐inflammatory M2 subtype in Hrg −/− mice. Upon chronic liver damage induced by CCl4 or methionine‐choline‐deficient (MCD) diet, liver injury and fibrosis were attenuated in Hrg −/−, compared to WT, mice. Macrophage populations were reduced and skewed toward M2 polarization in injured livers of Hrg −/− mice. Moreover, HRG‐deficient mice showed significantly enhanced hepatic vascularization by micro‐computed tomography and histology, corroborating proangiogenic activities of M2‐polarized liver macrophages. Purified HRG protein induced, but HRG‐deficient serum prevented, M1 macrophage differentiation in vitro . Accordingly, Hrg −/− mice transplanted with Hrg +/+ bone marrow, but not Hrg −/− ‐transplanted Hrg +/+ mice, remained protected from experimental steatohepatitis. Consistent with these findings, patients with chronic hepatitis C and nonalcoholic steatohepatitis significantly up‐regulated hepatocytic HRG expression, which was associated with M1 polarization of adjacent macrophages. Conclusions: Liver‐derived HRG, similar to alarmins, appears to be an endogenous molecular factor promoting polarization of hepatic macrophages toward the M1 phenotype, thereby promoting chronic liver injury and fibrosis progression, but limiting angiogenesis. Therefore, controlling tissue levels of HRG or PGF might be a promising strategy in chronic inflammatory liver diseases. (Hepatology 2016;63:1310‐1324)